Improvement of the Plantation Success in a Crib Wall in a Mediterranean Hydro-Meteorological Risks Scenario—Practical Results - Albert Sorolla (MDPI AG, 2021)
Due to the clime change scenario, severe hydro-meteorological phenomena are having a high impact on the ecosystems of the earth. Some strategies based on the use of natural communities associated with geomorphological changes that restore the natural landscape are gaining success due the resistance and resilience against damages. All of these strategies are known as nature-based solutions (NBS). Soil and water bioengineering techniques are one of the most appreciated tools to reach effectiveness for slope stabilization. They are based on the capacity of some plants to consolidate the soil with his rooting system in special conditions (high slope, flooding impact). Slope stabilization solutions with soil and water bioengineering techniques need to be adapted to this new scenario. Crib wall is one of the most complete soil and water bioengineering technique for structural slope stabilization. It is based on a wooden box full of live plants that in the future will grow and gain stability at the same time that wood decays. The crib wall box is full of soil, and the front area is traditionally stabilized with some branches of fascines to let plants grow, maintaining the structure. Fascines are made of branches of riparian species with the capacity for vegetative propagation. Their diameter can change due to the humidity variation, so the stiffness of the system is at risk against severe hydro-meteorological phenomena. This study aims to assess that the introduction of HDCL in crib walls improves planting success and makes them more resistant to adverse weather events in Mediterranean areas. Four experiments were performed in controlled and natural conditions with this proposal. The results show that the use of natural fibers instead of branch fascine helps to maintain the humidity conditions and increase the resistance capacity. High-density coir logs (HDCL) are not affected by volume changes for humidity conditions. HDCL maintains the plant’s humidity conditions longer and makes plants grow faster, bigger and increase their survival. This method of Crib wall construction increases the associated biodiversity. The most important results are that the use of HDCL in crib walls has an effect on the growth of planted shrub, the development of roots, the colonization of native vegetation and ultimately, the resistance of the structure to the floods. The results also show that crib walls are a good technique for the stabilization of slopes with considerable gradients and high hydraulic impacts. HDCL can reduce the water stress of plantations, and they can be a good system to retain runoff and provide it to the plants. Finally, the HDCL allows the revegetation of a crib wall 30% faster than with branch fascine.